The Impact of Using Chatbots in Improving Customer Service in The E-commerce Industry - Wakhidatus Solikhah, Efa; Ngetich, Brian Kiprop (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
The advancement of digital technology has encouraged e-commerce industry players to adopt artificial intelligence-based innovations, one of which is chatbots, as a strategy to improve the quality of customer service. This study aims to analyze the impact of using chatbots on customer satisfaction, service effectiveness, and user loyalty in the e-commerce sector. The method used is quantitative with a survey approach to 120 respondents who are active users of e-commerce platforms in Indonesia. The results of the study show that the use of chatbots significantly increases the speed of response, 24/7 service availability, and ease of access to information which has a positive impact on customer satisfaction. In addition, chatbots also contribute to increasing operational efficiency and reducing the workload of conventional customer service. However, the limitations of chatbots in handling complex problems are still an obstacle that affects user perceptions of service personalization. These findings provide important implications for e-commerce managers to continue to develop more adaptive, responsive, and humane chatbot features in order to improve the quality of interactions with customers in a sustainable manner.